Reflection Strategies on Students' Thinking Structures in the Mathematical Problem Solving Steps - Elly Susanti (MEJ (Mathematics Education Journal), 2021)
Thinking is a process of understanding various things encountered in everyday life, finding certain opinions or ideas, making judgments, and solving problems. One of the tasks teachers must do in learning mathematics is to help students convey the cognitive processes experienced when solving issues. The thinking errors are and the algorithms that are not yet complete in solving student problems. But in reality, students still have difficulties that cause errors in solving mathematical problems. This study describes the reflection strategy on thinking to correct students' misconceptions in solving mathematical problems. This type of research is descriptive research with a qualitative approach. Research data consists of student answers, results think aloud, and the results of semi-structured interviews. The results showed that students with low problem-solving abilities experienced assimilation at the stage of understanding the problem only. In contrast, at the scene of developing strategies and implementing plans, accommodation occurred. The students will attack because students can decompose problems into simpler ones but require reflection to connect mathematical material to solve problems. In addition, students also need thinking to correct errors and complete incomplete algorithms when carrying out plans for solving mathematical problems. Keywords: reflection strategy, thinking structure, mathematical problem solving